Intestinal absorption and biliary elimination of glycyrrhizic acid diethyl ester in rats - Koga K; Kawamura M; Iwase H; Yoshikawa N (Dove Medical Press, 2013)
Kenjiro Koga,1 Mayuri Kawamura,1 Hiroshi Iwase,2 Nobuji Yoshikawa31Department of Clinical Pharmaceutics, Faculty of Pharmaceutical Sciences, Hokuriku University, Kanazawa, 2Research Division, 3Research and Development Division, Cokey Systems Co, Ltd, Matsusaka, JapanBackground: The purpose of this study was to evaluate absorption and elimination from the gastrointestinal tract of glycyrrhizic acid diethyl ester (GZ-DE) which was prepared as a prodrug of glycyrrhizic acid (a poorly absorbed compound) in rats.Methods: After the GZ-DE solution was administered via the intravenous, intraduodenal, intraileal, and stomach routes, GZ-DE and GZ concentrations in bile were determined by high-performance liquid chromatography. The stability of GZ-DE was estimated from residual GZ-DE and GZ produced in GZ-DE solutions prepared with distilled water, a pH 1.2 solution, 0.9% NaCl solution, and phosphate-buffered solution (pH 7.4) at 37°C.Results: GZ-DE was eliminated into bile by the pharmacokinetic parameters of apparent distribution rate constant (4.56 ± 0.36 per hour) and apparent elimination rate constant (0.245 ± 0.042 per hour). After intravenous and intraduodenal administration of GZ-DE, the concentration ratio of GZ-DE to GZ in bile was approximately 4:1, and the bioavailability of GZ containing GZ-DE was three-fold higher compared with the bioavailability of GZ after intraduodenal administration. GZ-DE was immediately precipitated in pH 1.2 solution and was converted to GZ by hydrolysis in pH 7.4 solution.Conclusion: Improvement of intestinal absorption of GZ was made possible by administration of GZ-DE into the intestine where absorption of GZ is lower than in the strong acidic environment of the stomach. However, because the elimination rate in bile simulated from kinetic parameters of GZ-DE was higher than the conversion rate from GZ-DE to GZ by hydrolysis, it is thought that the availability of GZ as a revolutionary prodrug was not high from the viewpoint of bioavailability of GZ in the liver by intestinal administration of GZ-DE.Keywords: glycyrrhizic acid, prodrug, intestinal absorption, bile elimination, pharmacokinetics, rat